Analisis Pengaruh Konsumsi, Investasi, dan Inflasi Terhadap Produk Domestik Bruto di Indonesia Tahun 2000-2012 - Yudisthira, I Made; Budhiasa, I Gede Sujana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
Economic development in a country, basically aims to achieve social prosperity through economic growth, and economic development among these there are linkages between national and regional development close to each other, thus forming a strong economy, strong, and evenly. Economic development is not just struggling to think and worry about how to achieve high economic growth. Development was to improve the quality of life and well-being of society. Economic growth alone is measured by Gross Domestic Product (GDP). The purpose of this research was to determine the effect of consumption, investment, and inflation to Gross Domestic Product (GDP). The research was conducted in Indonesia from 2000 to 2012 in the form of quarter as much data as the number 52. This research used Two Stage Least Square (TSLS) as an analytical technique. Based on the analysis, it was found that consumption and investment, are significantly positive toward GDP models, while inflation is positive but not significant toward GDP. Consumption is significantly positive towrd investment model, while the inflation variable is positive but not significant toward investment model. Inflation is positive but not significant toward consumption models.
Keywords: produk domestik bruto; konsumsi; investasi; inflasi